2012
DOI: 10.4103/2141-9248.96934
|View full text |Cite
|
Sign up to set email alerts
|

Surgical-site infection following cesarean section in Kano, Nigeria

Abstract: Objectives:To determine the prevalence, risk factors and common bacterial pathogens for surgical site infection (SSI), following cesarean section (CS).Materials and Methods:A retrospective case-control study of patients delivered by CS in Aminu Kano Teaching Hospital, Kano, Nigeria. The cases were the patients whose CS was complicated by SSI; they were matched by other patients delivered by CS who had had no SSI as controls. Hospital records of cases and controls were compared.Results:Four hundred and eighty f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

39
80
6
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(136 citation statements)
references
References 12 publications
39
80
6
4
Order By: Relevance
“…The study discovers that the SSIs incidence rate of 19.6% based on bacteriological criteria is contrary to 38% WHO (2011). The study findings is also consistent with 22% incidence rate in OAUTHC, (Ohajuru, 2010),but contrary to 9.1% incidence at AKTH Kano, (Jido & Garba, 2012). …”
Section: Discussion Of Findingssupporting
confidence: 80%
See 2 more Smart Citations
“…The study discovers that the SSIs incidence rate of 19.6% based on bacteriological criteria is contrary to 38% WHO (2011). The study findings is also consistent with 22% incidence rate in OAUTHC, (Ohajuru, 2010),but contrary to 9.1% incidence at AKTH Kano, (Jido & Garba, 2012). …”
Section: Discussion Of Findingssupporting
confidence: 80%
“…The study revealed that most of the subjects are in the age group between 21-30 years and showed a female preponderance .Similar demographic observation was reported by another study in Aminu Kano Teaching Hospital Kano, Nigeria (Jido & Garba, 2012).The rate of SSI was significantly higher in female subjects than in male .This could be explained by multiple risk factors in females such as high caesarean section rate and high BMI.…”
Section: Discussion Of Findingssupporting
confidence: 73%
See 1 more Smart Citation
“…Out of the 350 patients recruited for this study, 9.1% had SSI, a rate that is similar to the findings of previous studies in Nigeria 3,4 . The male preponderance (62.5% of cases) is also in agreement with the findings of others 10 .…”
Section: Discussionsupporting
confidence: 78%
“…In the United States, SSI is found to be a serious complication with an incidence of 2 to 5% in patients undergoing surgery 2 while in Nigeria, it was found to be 9.4 and 9.1% at Ibadan and Kano respectively 3,4 . SSI has been reported to be second only to urinary tract infection as the commonest hospital acquired infection and actually the most commonly encountered form of nosocomial infection in surgical practice 5 .…”
Section: Introductionmentioning
confidence: 99%